Pulses for Nutritional Security and Ecological Sustainability - Singh, SK; Praharaj, CS (Indian Journal of Extension Education, 2021)
The country is continuing striving for increasing genetic gains through novel technologies, like transgenicÂ technology, incorporating photo-thermal insensitivity and breeding short-duration varieties for increasing cropping intensity, conservation agriculture and strategic practicable technologies, research on storage structures and minimizing post harvest losses, promoting participatory and demand driven research including valueÂ addition and appropriate policy support. All these again oriented towards reducing cost of production and enhancing income through scaling productivity so as to double the farm income by 2022.